2012
DOI: 10.1007/s00464-012-2154-2
|View full text |Cite
|
Sign up to set email alerts
|

The use of novel hemostatic sealant (Tisseel®) in laparoscopic myomectomy: a case–control study

Abstract: The use of Tisseel during LM may represent a valid alternative solution for obtaining hemostasis, reducing intra- and postoperative bleeding. Furthermore, it may help the surgeon to obtain a rapid healing of the injured surfaces, probably reducing the use of electrocoagulationand traumatisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The use of HA during laparoscopic gynecologic procedures was evaluated in 1 study involving myomectomy, 5 studies in adnexal procedures (including cystectomy, sterilization, and salpingotomy for ectopic pregnancy), 1 study during sterilization, and 1 study for repair of uterine perforation. 1421 No studies evaluating HA use at time of laparoscopic hysterectomy for benign indication were found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of HA during laparoscopic gynecologic procedures was evaluated in 1 study involving myomectomy, 5 studies in adnexal procedures (including cystectomy, sterilization, and salpingotomy for ectopic pregnancy), 1 study during sterilization, and 1 study for repair of uterine perforation. 1421 No studies evaluating HA use at time of laparoscopic hysterectomy for benign indication were found.…”
Section: Resultsmentioning
confidence: 99%
“…The same study observed a significant reduction in operative time when the fibrin sealant was used ( p < .05). 14 Another type of fibrin sealant, Tachosil (Baxter Healthcare Corporation, Deerfield, IL, USA), was evaluated in a prospective cohort study of 129 with respect to potential benefits on ovarian reserve during laparoscopic ovarian cystectomy. Floseal (Baxter Healthcare Corporation, Deerfield, IL, USA), a thrombin-gelatin matrix, was another agent of interest in this article.…”
Section: Resultsmentioning
confidence: 99%
“…In another historically controlled ( n = 15) prospective series of patients ( n = 15) over 2 years, fibrin sealant was used as an adjunct to hemostasis on uterine closure sutures during laparoscopic myomectomy [282]. Significant benefit to using fibrin sealant was noted for operative time (47.7 versus 62.1 min, P < 0.05), time to achieve complete hemostasis (195.5 versus 361.8 sec, P < 0.0001), estimated blood loss (111.3 versus 230 mL, P < 0.05), and mean decrease in hemoglobin (1.36 versus 2.04 g/dL, P < 0.05).…”
Section: Less Frequently Published Clinical Applications Of Fibrinmentioning
confidence: 99%
“…The postoperative hemoglobin (Hb) change is an objective parameter of intraoperative blood loss after LM [4, 5, 8, 18, 21, 23] and correlates better with the actual blood loss than a subjective estimation [24]. Studies on predictors of intraoperative blood loss in LM are rare.…”
Section: Introductionmentioning
confidence: 99%